Nation-wide Food Safety Assurance Program to Prevent Food Detention by Importing Country - Sri Rahardjo (Indonesian Food and Nutrition Progress, 1998)
The FDA's data indicate that some Indonesian food export to the U.S. have been subjected to automatic de- tention and no sign of declining within the last 13 months (April 1997 – April 1998). This status was based on past hystory of the Indonesia commodity which failed to meet the existing requirements. Cocoa beans exporters were among the most frequent violators, followed by the tuna and shrimp manufacturers or exporters. The new HACCP -based requirement especially for imported fish which became effective since December 18, 1997 would certainly pose significant problem which could under- mine the nation ability to overcome the current economic crises. Systematic programs have to be developed and correctly deployed to meet the strict requirements demanded by the importing country. The objective of the proposedPartnership in Food Safety Assurance program is to assure that all processed foods including fish and fishery product and the condition under which these foods are manufactured will result in safe food. The primary intention of the proposed program is to focus on the food manufacturing facilites and their links to incoming raw materials and shipment of finished products.